Implementation of Digital Presence in Enforcing Employee Work Discipline at Perumdam Tirta Waesai Barru - Naufal Nisphu Ramadhan; Sirajuddin Saleh; Hasyim, Nasaruddin (Pendidikan Administrasi Perkantoran, UNM, 2025)
The digital attendance system in enforcing employee work discipline at Perumdam Tirta Waesai Barru offers an effective solution to disciplinary and fraud problems that often occur in manual systems, with benefits such as increased transparency, administrative efficiency, and support for employee performance. This study aims to determine the implementation of digital attendance in enforcing employee work discipline at Perumdam Tirta Waesai Barru. The research is qualitative, using data collection techniques through observation, interviews and documentation. The results of this study indicate that the implementation of digital attendance in enforcing employee work discipline at Perumdam Tirta Waesai Barru is running